An examination of billboard impacts on crashes on a suburban highway: Comparing three periods—Billboards present, removed, and restored. (25th November 2019) - Gitelman, Victoria; Doveh, Etti; Zaidel, David
Abstract: Objective: Advertisement billboards on roadsides distract drivers from driving tasks and may increase the risk of crashes. Yet, empirical evidence on the direct impact of advertisement signs on crashes is scarce. The Ayalon Highway in Israel is a suburban highway crossing the greater Tel Aviv–Yafo metropolitan area. Following debates in parliament, advertising billboards were removed from the road in 2008 and restored mid-2009. This study examined the impact of advertising billboards on crashes while considering 2 interventions: Removing (or covering) existing billboards and their subsequent restoration. Method: Three periods of billboard presence were defined: Period 0, when billboards were visible; period 1, when billboards were removed; and period 2, when billboards became visible again. Crash changes associated with each intervention were estimated by comparing period 1 vs. period 0 and period 2 vs. period 1, respectively, and by comparing vs. control groups. Negative-binomial regression models were fitted to the monthly crash counts, while controlling for time period, site group (treatment or control), and seasonal effect. Results: Removing the billboards was associated with a decrease of 30 to 40% in injury crashes and restoring the billboards was associated with an increase of 40 to 50% in injury crashes. The crash changes were consistent across various analyses. The estimated decrease in crash numbers during the removal period was up to 100 damage-only crashes and 50 injury crashes per year, and the estimated increase in crashes after billboard restoration was up to 120 damage-only crashes and 30 injury crashes a year. Conclusion: The study provided empirical evidence on the positive safety impact of removing billboard advertising from the roadsides of a suburban highway and of the negative safety impact of billboard restoration. The stronger impact values found in the study, compared to previous research, may be related to the high frequency of conspicuous billboards along the road and to complicated traffic conditions on the road—a heavily traveled route with a high density of interchanges—that might strengthen the negative impact of driver distraction due to advertising billboards.